2015
DOI: 10.1007/s10802-015-9999-5
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent-Parent Attachment and Externalizing Behavior: The Mediating Role of Individual and Social Factors

Abstract: The aim of this study was to test whether the associations between adolescent-parent attachment and externalizing problem behavior of adolescents were mediated by adolescent cognitive distortions, self-esteem, parental monitoring and association with deviant peers. A total of 102 adolescents (71 % male; aged 12–19 years) at risk for developing delinquent behaviors reported on attachment, parental monitoring, aggressive and delinquent behavior and peers. Mediation effects were tested by using structural equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 100 publications
(117 reference statements)
3
42
0
8
Order By: Relevance
“…In the literature, no studies have been reached examining the relationship between parental attitude and children's play behaviors. However, there are studies indicating that there is a significant relationship between parental attitude and children's social competence behaviors (Andı, 2014;Coplan et al, 2002;Çetinkaya, 2016;de Vries et al, 2016;Jiménez-Barbero et al, 2016;Ogelman et al, 2013;Yener, 2014). In these studies, it was concluded that democratic parental attitude increases children's social competence behaviors, authoritarian and permissive attitude increases children's anxiety-introversion and anger-aggression behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, no studies have been reached examining the relationship between parental attitude and children's play behaviors. However, there are studies indicating that there is a significant relationship between parental attitude and children's social competence behaviors (Andı, 2014;Coplan et al, 2002;Çetinkaya, 2016;de Vries et al, 2016;Jiménez-Barbero et al, 2016;Ogelman et al, 2013;Yener, 2014). In these studies, it was concluded that democratic parental attitude increases children's social competence behaviors, authoritarian and permissive attitude increases children's anxiety-introversion and anger-aggression behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Privrženost, koju je Ainsworth (1989) okarakterizirala kao dugotrajnu emocionalnu vezu koju dijete razvija s primarnim skrbnikom (najčešće majkom), u mnogim se istraživanjima pokaza-la značajnom za psihosocijalni razvoj adolescenata. Tako je slabija, odnosno nesigurna, privrženost (ovisno o konceptualizaciji i instrumentu mjerenja privrženosti) povezana s više agresivnih i delinkventnih ponašanja te općenito eksternaliziranih problema adolescenata (De Vries, Hoeve, Stams i Asscher, 2016;Lucktong, Salisbury i Chamratrithirong, 2018;Ručević, 2011). Štoviše, metaanaliza Fearon, Bakermans-Kranenburg, Van IJzendoorn, Lapsley i Roisman (2010), koja je uključivala radove o povezanosti privrženosti roditeljima i eksternaliziranih ponašanja kod djece do 12 godina, pokazala je da postoji umjerena veličina učinka te povezanosti.…”
Section: Uvodunclassified
“…Confirma-se, em novas gerações, o efeito negativo de vinculações inseguras aos pais -operacionalizadas aqui por menores valores nas dimensões "Confiança-proximidade afetiva" e "Comunicação" com aos pais, e maior perceção de "Rejeição" da parte dos pais. Representações negativas das relações com os pais conduzem a expectativas de que não poderão contar com eles para a resolução das suas angústias, propiciando, por seu turno, representações negativas de si próprio (como não merecendo ser apoiado, ou compreendido pelas figuras significativas); exprimindo-se esse mal-estar, eventualmente, por perturbações externalizadas e/ou internalizadas, consoante o sujeito (Al-Yagon, Kopelman-Rubin, Klomek, & Mikulincer, 2016;Follan & Minnis, 2009;de Vries, Hoeve, Stams, & Asscher). Um dado interessante neste estudo foi a constatação do acordo entre a perceção dos problemas de comportamento reportados pelos pré-adolescentes e a perceção dos seus pais sobre esses mesmos comportamentos -concordância expressa nas correlações significativas encontradas entre avaliações dos filhos, e avaliações dos pais sobre a magnitude dos problemas de comportamento.…”
Section: Correlações Entre Dimensões Do Ippa-r E Dimensões Sdqunclassified
“…Para além destas variáveis, as representações construídas na infância (i.e., os modelos operantes internos do self e relações) serão atualizados, não apenas por eventuais alterações nas condições de vida, como pela revisão de representações passadas, (re)interpretadas agora à luz de novas competências cognitivas, como a "teoria da mente", e, mais tarde, pelo acesso ao pensamento formal (Machado, 2003), que permite novas formas de reanalisar experiências anteriores (Arranz, Artamedi, Olabarrieta, & Martín, 2002). Porém, os padrões inseguros de vinculação podem desencadear mecanismos defensivos que induzem exclusões de informação, e/ou incapacidade para integrar diferentes tipos de informação acerca das experiências vinculativas (Al-Yagon, Kopelman-Rubin, Klomek, & Mikulincer, 2016;de vries, Hoeve, Stams, & Asscher, 2016), num processo que "alivia o self da culpa, e do autoconceito negativo" (de vries et al, 2016). Como as vinculações inseguras levam a maior relutância em partilhar experiências com os pais, menor monitorização, e menor comunhão de vivências, o afastamento/rejeição torna-se, para esses, mais provável, mesmo que os próprios (i.e., filhos e pais) não se apercebam a priori.…”
unclassified